Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c7cc01605k
|View full text |Cite
|
Sign up to set email alerts
|

Selective perrhenate recognition in pure water by halogen bonding and hydrogen bonding alpha-cyclodextrin based receptors

Abstract: Alpha-cyclodextrin based anion receptors functionalised with pendant arms containing halogen and hydrogen bond donor motifs display selective association of perrhenate in aqueous media at neutral pH. NMR and ITC anion binding investigations reveal the halogen bonding receptor to be the superior host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 32 publications
0
38
0
2
Order By: Relevance
“…Notable exceptions are cyclopeptides and bis-cyclopeptides, reported by Kubik et al,t hat are able to bind highly hydrated anions, such as sulfate, in water due to their extremelyp re-organised concave arrangement of polarised peptide NÀHf ragments. [14,15] As af urther possibility,p ositive charges inside the cavity of the receptor can be generated through the inclusiono fm etal ions. [14,15] As af urther possibility,p ositive charges inside the cavity of the receptor can be generated through the inclusiono fm etal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Notable exceptions are cyclopeptides and bis-cyclopeptides, reported by Kubik et al,t hat are able to bind highly hydrated anions, such as sulfate, in water due to their extremelyp re-organised concave arrangement of polarised peptide NÀHf ragments. [14,15] As af urther possibility,p ositive charges inside the cavity of the receptor can be generated through the inclusiono fm etal ions. [14,15] As af urther possibility,p ositive charges inside the cavity of the receptor can be generated through the inclusiono fm etal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Theremarkable enhancement of halide complexation by XB 1·PF 6 rotaxane by at the very least three orders of magnitude in comparison to HB rotaxane 14·PF 6 illustrates again the superiority of halogen bonding over hydrogen bonding in aqueous anion recognition. [7,9,[12][13][14][15] Finally,inaneffort to elucidate the effect of incorporating the perfluoroaryl motif into the axle component of 1·PF 6 ,the halide anion binding properties of monocationic XB rotaxane 15·PF 6 were determined (Table 3Entry 3). As expected, 1·PF 6 demonstrates notable enhancement of halide binding,w ith the strength of iodide complexation at least two orders of magnitude greater than 15·PF 6 rotaxane ( Table 3, Entry 1and 3), which can be attributed to the rigid, electron deficient and hydrophobic nature of the perfluoroaryl substituents of the pyridinium bis-iodotriazole axle component of 1·PF 6 ,f acilitating in particular the amplified potencyo fX Bd onorhalide anion interactions.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1][2][3][4][5][6] Regarding the latter,w ea nd others have demonstrated that XB hosts often display superior anion affinities and contrasting selectivities in comparison to HB host analogues. [12,13] This is especially the case with elaborate XB mechanically interlocked molecules (MIMs), which due to their unique topological three-dimensional and highly preorganized cavities are capable of aqueous anion recognition. [12,13] This is especially the case with elaborate XB mechanically interlocked molecules (MIMs), which due to their unique topological three-dimensional and highly preorganized cavities are capable of aqueous anion recognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, some supramolecular hosts have been designed to bind perrhenate in a very selective manner, however, their operations are limited to organic media or organic/aqueous mixtures . To overcome this limitation, recently, some supramolecular receptors have been synthesized that utilize a combination of electrostatic interactions and multiple hydrogen‐bonding interactions and, more recently, halogen bonding to achieve the selective binding of the perrhenate anion in aqueous media . To exploit the selective binding of the designed supramolecular host with the perrhenate/pertechnetate anion for its analytical detection, one such receptor molecule was functionalized with a fluorophore, anthracene, which signaled the binding of the perrhenate/pertechnetate to the receptor molecule through a decrease in its fluorescence intensity .…”
Section: Introductionmentioning
confidence: 99%